A role for everolimus in post‐transplant encapsulating peritoneal sclerosis: First case report. (April 2014) - Sud, Rahul; Garry, Lorraine; Spicer, Stephen Timothy; Allen, Richard DM; Eris, Josette M; Wyburn, Kate; Verran, Deborah; Cooper, Caroline Louise; Chadban, Steve
Abstract: Encapsulating peritoneal sclerosis (EPS) is a rare complication of peritoneal dialysis (PD) that carries a high morbidity and mortality. The 'two hit theory' suggests that long term deterioration of the peritoneum combined with intraperitoneal inflammation is needed in the pathogenesis of EPS. For unclear reasons, post transplantation EPS is being increasingly reported in patients previously on PD. To date, there is no proven effective therapy with an absence of randomised controlled trials. Individual case reports and small case series have reported on the use of tamoxifen and corticosteroids for medical management of EPS. The use of everolimus has been reported in a single case, and never in the setting of renal transplantation. Here, we present the first case of post‐transplant encapsulating peritoneal sclerosis treated successfully with a combination of everolimus, tamoxifen, low dose corticosteroid and surgery.